Cystine levels, cystine flux, and protein catabolism in cancer cachexia, HIV/SIV infection, and senescence - Hack, Volker; Breitkreutz, Raoul; Drings, Peter; Kinscherf, Ralf; Taut, Friedemann; Holm, Eggert; Dröge, Wulf (The FASEB journal, 1997)
Patients with skeletal muscle catabolism (cachexia) fail to conserve the skeletal muscle protein and release large amounts of nitrogen as urea. Previous studies suggest that the threshold for the conversion of amino acids into other forms of chemical energy and the concomitant production of urea are regulated by the plasma cystine level and hepatic cysteine catabolism. Studies of plasma amino acid exchange rates in the lower extremities now show that healthy young subjects regulate their plasma cystine level in a process that may be described as controlled constructive catabolism. The term controlled describes the fact that the release of cystine and other amino acids from the peripheral tissue is negatively correlated with (certain) plasma amino acid levels. The term constructive describes the fact that the release of cystine is correlated with an increase of the plasma cystine level. The regulation of the plasma cystine level is disturbed in conditions with progressive skeletal muscle catabolism including cancer, HIV infection, and old age. These conditions show also a low plasma glutamine:cystine ratio indicative of an impaired hepatic cystine catabolism. In HIV+ patients and SIV-infected macaques, a decrease of the plasma cystine level was found to coincide with the decrease of CD4+ T cells.
Gesehen am 16.10.2017